Postsynthetic Incorporation of a Singlet Oxygen Photosensitizer in a Metal–Organic Framework for Fast and Selective Oxidative Detoxification of Sulfur Mustard. Issue 1 (22nd November 2016) - Howarth, Ashlee J.; Buru, Cassandra T.; Liu, Yangyang; Ploskonka, Ann M.; Hartlieb, Karel J.; McEntee, Monica; Mahle, John J.; Buchanan, James H.; Durke, Erin M.; Al‐Juaid, Salih S.; Stoddart, J. Fraser; DeCoste, Jared B.; et al.
Abstract: A fullerene‐based photosensitizer is incorporated postsynthetically into a Zr6 ‐based MOF, NU‐1000, for enhanced singlet oxygen production. The structural organic linkers in the MOF platform also act as photosensitizers which contribute to the overall generation of singlet oxygen from the material under UV irradiation. The singlet oxygen generated by the MOF/fullerene material is shown to oxidize sulfur mustard selectively to the less toxic bis(2‐chloroethyl)sulfoxide with a half‐life of only 11 min. Abstract : Overcoming darkness, with light : Light‐emitting diodes (LEDs) are used to generate singlet oxygen from a metal–organic framework which has been post‐synthetically modified to include fullerene in the mesoporous channels. By using the singlet oxygen generated from the MOF, sulfur mustard (HD) is oxidized selectively to less toxic sulfoxide products with a half‐life of only 11 minutes. This is the fastest half‐life observed so far using this safe and practical photo‐oxidation method for detoxifying the chemical warfare agent HD.